Computer Vision of Optimal Geometric Concentration Ratio for the Solar Ball Lens - Hadi, Sabah M.; Abdullah, Manal M.; Mahdi, Mohamed S. (Iraqi Journal of Science, 2022)
This research evaluates the optical properties of an inhomogeneous and non-paraxial system using a solar ball lens (SBL) as a new thermal solar concentrated collector. This evaluation is based on detecting a diacaustic curve in a straightforward and accurate manner, with the diagnostic relying on image processing as a computational tool using the MATLAB program rather than a complicated numerical analytic procedure. The circle of least confusion (CLC) of the (SBL), (Fluorinated ethylene propylene (FEP) polymer – water core), was calculated. Furthermore, the study evaluated the maximum geometrical concentration ratio (G C) of refracted solar radiation that can be captured by a receiver of the (SBL). Without energy losses due to spherical aberration, the (G C) ratio was (14.10) at (h/r) ratio, circular aperture radius to ball radius, around (0.6). The investigation also revealed an aplanatic point for preventing the development of optical envelope inside the solar ball lens at (h/r) equal to 0.8638, as well as a maximum (h/r) value of 0.7351 for collecting solar radiation.